Sociedade Brasileira de Defesa da Tradição, Família e Propriedade (TFP): um movimento ultramontano na Igreja Católica do Brasil? - Santos Júnior, João Geraldo dos (2008)
This paper discusses the institution TFP and repeats, in principle, the history of the Catholic Church in Brazil and the world in the years preceding the founding of the TFP (1960). The purpose of this is precisely analyze the TFP as a movement within the Catholic Church over the years that lived its founder, Plínio Corrêa de Oliveira. Although externally Catholic, the TFP, often showed discrepancies between their ideas and practices and preaching of the Church. It then traditional ultramountainous movement or a sect? Simply say that the TFP has been a ultramountainous sanctuary or a sectarian or not to characterize correctly, because they are different concepts, and theoreticalment incompatible, but that seemed TFP reconcile internally, making it and odd move, with characteristic very own. This work used in its analysis of the references your TFP, as well as works published by egresses the institution, in addition to books of authors who generally already discussed the issue and Ultramountainism or sect in other contexts. The TFP, considered in this study, was officially Catholic, the Church never has spoken to the contrary, had strong sectarian characteristics and even time of the traditional Ultramountainism was thus a movement, not classifiable generalized manner, but only in their postures